The Implementation of Peer Group Counseling Method in Strengthening Mental Health Among Adolescents to Support the Healthy School Movement - Indah Kurniawati; Miftahul Hakiki; Nurul Eko Widyastuti; Indah Christiana; Wahyu Fuji Hariani (Universitas Tribhuwana Tunggadewi, 2026)
Adolescent mental health remains a significant public health concern. The 2022 Indonesia National Adolescent Mental Health Survey reported that approximately 34.9% of Indonesian adolescents experienced mental health problems, whereas only a small proportion accessed counseling services. This study aimed to examine changes in adolescent mental health scores following the implementation of peer group counseling as part of the Healthy School Movement. A quantitative pre-experimental study with a one-group pre-test–post-test design was conducted among 30 students at MAN 1 Banyuwangi from August to October 2025. Participants were selected using stratified sampling based on age and grade level. Mental health was measured before and after the intervention using the Mental Health Inventory questionnaire. Descriptive analysis was used to present the distribution of mental health categories, while a paired-sample t-test was performed to examine differences between pre-test and post-test scores. The results showed that the proportion of adolescents in the poor mental health category decreased from 53.3% before the intervention to 26.6% after the intervention. Conversely, the proportion in the moderate mental health category increased from 43.3% to 66.6%, while the proportion in the good category increased from 3.3% to 6.6%. The mean mental health score increased by 11.47 points after peer group counseling, and the difference was statistically significant (t = ?4.852; p 0.001). The estimated effect size was large (Cohen’s d = 0.89), indicating a substantial within-group improvement. Peer group counseling was associated with improved adolescent mental health scores and may be considered a supportive school-based strategy within the Healthy School Movement. However, because this study involved a small sample and did not include a control group, the findings should be interpreted cautiously.